Robust effects of stress on early lexical representation. (29th May 2020) - Segal, Osnat; Keren‐Portnoy, Tamar; Vihman, Marilyn
Abstract: This study aims to elucidate the factors that affect the robustness of word form representations by exploring the relative influence of lexical stress and segmental identity (consonant vs. vowel) on infant word recognition. Our main question was which changes to the words may go unnoticed and which may lead the words to be unrecognizable. One‐hundred 11‐month‐old Hebrew‐learning infants were tested in two experiments using the Central Fixation Procedure. In Experiment 1, 20 infants were presented with iambic Familiar and Unfamiliar words. The infants listened longer to Familiar than to Unfamiliar words, indicating their recognition of frequently heard word forms. In Experiment 2, four groups of 20 infants each were tested in each of four conditions involving altered iambic Familiar words contrasted with iambic Unfamiliar nonwords. In each condition, one segment in the Familiar word was changed—either a consonant or a vowel, in either the first (unstressed) or the second (stressed) syllable. In each condition, recognition of the Familiar words despite the change indicates a less accurate or less well‐specified representation. Infants recognized Familiar words despite changes to the weak (first) syllable, regardless of whether the change involved a consonant or a vowel (conditions 2a, 2c). However, a change of either consonant or vowel in the stressed (second) syllable blocked word recognition (conditions 2b, 2d). These findings support the proposal that stress pattern plays a key role in early word representation, regardless of segmental identity.